Հանրահաշիվ

291
ա)(x+y)+a(x+y)-2(x+y)=(x+y)(a+3)
բ)m(a-b)-n(b-a)+(3a-3b)=(a-b)(m+n+3)m(a-b)+n(a-b)+(3a-3b)=(a-b)(m+n+3)
գ)(2m-6n)+(xm+3xn)-y(3n-m)=(m-3n)=2(m-3n)+x(m-3n)+y(m-3n)=(m-3n)(2+x+y)
դ)(6x-15y)-(5y-2x)+(2ax-5ay)=(2x-5y)=3(2x-5y)+(2x-5y)+a(2x-5y)(4+a)
ե)(-am-bm)+(3a+3b)-(x²a+x²b)=(a+b)=-m(a+b)+3(a+b)-x²(a+b=(a+b)(-m+3-x²)

293.

9a²-4=(3a-2)(3a+2)

25x²-1=(5x-1)(5x+1)

1/4m²-16n²=(1/2m-4n)(1/2m+4n)

100a²-0,25b²=(10a-0,5b)(10a+0,5b)

x¹²-y2=(x⁶-y)×(x⁶+y)

m⁶-n⁶=(m³-n³)×(m³+n³)

Թողնել պատասխան

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Փոխել )

Google photo

You are commenting using your Google account. Log Out /  Փոխել )

Twitter picture

You are commenting using your Twitter account. Log Out /  Փոխել )

Facebook photo

You are commenting using your Facebook account. Log Out /  Փոխել )

Connecting to %s